Vulgarismen in deutschen und polnischen Rap- und Rocksongs. Eine semantische und strukturelle Analyse - Małgorzata Derecka (Linguistische Treffen in Wrocław, 2022)
Those who fear the decline of the German language use the following argumentation: countless foreign words in the German language system, patchwork-like language use with all its linguistic phenomena, such as abbreviations and short forms, multilingualism, code-switching, bricolage, hybrid formations and borrowings, grammatical reduction and deviation from grammatical norms, codification of the language. Many of these language-changing processes are explained and even justified by globalisation and the enormous mobility of people in today’s world. There is somewhat less understanding of the use of vulgarisms not only in everyday life but also in the media. What was unthinkable a few decades ago has become reality today: Vulgarisms permeate public language and are even used by celebrities. While individual swear words no longer seem to shock, their accumulation in rock and rap lyrics is completely rejected by many or bypassed as a taboo subject. In his monograph, which is dedicated to a semantic and structural analysis of vulgarisms in German and Polish rap and rock lyrics, Krystian Suchorab deals with the use of vulgarisms and points out the following aspects, among others: vulgarisms and aggression in music; lyrics as a form of communication; semantic and structural analysis of vulgar lexemes in German and Polish rap and rock songs. With this contribution, the author breaks a taboo and enriches with his research the already existing, but not particularly extensive literature on the topic of vulgarisms. The topic still seems to be up-to-date and worth further research.